(untitled) - Filova, Eva; Sosedova, Jarmila; Jurkovic, Martin (Doprava a spoje, 2011)
The purpose of the rivers classification is the navigable distinctionaccording to vessels type or complete sets of vessels. At first, it serves for determination and unification of new and upgraded waterways. The categorization of watercourses and water areas, which create the primary tourist attractions in Slovakia for recreational sailing. Categorization of water currents in accordance to degree of difficulty for sport sailing.